(untitled) - Camp, Sue C. (Boston, 2001)
This text provides instruction and exercises designed to sharpen skills in detecting and correcting errors in written communication of all kinds. The material progresses from easy-to-recognize errors to those that are more difficult to spot.
Keywords: Proofreading,English language,Business writing; Business English